The frequency and clinical significance of nontarget superficial and deep vein occlusion after physician compounded foam sclerotherapy of varicose tributaries. (July 2020) - Lobastov, Kirill; Vorontsova, Athena; Bargandzhiya, Astanda; Tsaplin, Sergey; Schastlivtsev, Ilya; Barinov, Victor; Laberko, Leonid; Dvornikov, Anton
Objective: To evaluate the incidence and clinical relevance of silent nontarget occlusion (NTO) of superficial and deep veins occurring after ultrasound-guided foam sclerotherapy (UGFS) that can be detected by serial duplex ultrasound scan (DUS). Methods: This retrospective analysis evaluated the medical records of patients treated with UGFS at a private clinic in Moscow, Russia from 2015 to 2017. All patients underwent serial DUS at 1 to 2 weeks and 1, 3, 6, and 12 months after UGFS. Results: During the observation period, 268 patients were treated with UGFS, using physician compounded polidocanol foam 257 lower limbs of 196 patients (73%) with varicose veins who underwent DUS at 1 to 2 weeks after the last session of UGFS (inclusion time-point): 139 women and 57 men (mean age: 44.2 ± 12.2 years) with the following CEAP clinical class distribution: C2, 74.0%; C3, 20.0%; C4, 4.5%; and C5, 1.5%. NTO at the inclusion time-point occurred in 60 limbs (23.3%) of 57 patients (28.5%) and was symptomatic only in three limbs (1.2%). Most occlusions were localized in the untreated great saphenous vein trunk ( n  = 28) and the calf muscle veins ( n  = 23). Overall, 72%, 44%, 29%, and 10% of all limbs and 77%, 45%, 28%, and 12% of limbs with NTO were followed up by DUS at 1, 3, 6, and 12 months, respectively. There were no cases of thrombus progression or symptomatic venous thromboembolism (VTE). At six months, no deep vein occlusions persisted. Conclusions: The frequency of nontarget vein occlusion after UGFS revealed by serial DUS may be as high as 23.3%. These occlusions tend to resolve within six months and are not associated with symptomatic VTE.